Positive and Negative Emotional Eating Are Not the Same—The Spanish Version of the Positive-Negative Emotional Eating Scale (PNEES) - Manchón, Javier; Quiles, María José; Quiles, Yolanda; López-Roig, Sofía (Frontiers in Psychology, 2021)
The literature points to the importance of distinguishing between positive and negative emotional eating in relation to overeating and binge eating. The aim of this study was to evaluate the Spanish version of the Positive-Negative Emotional Eating Scale (PNEES) in a Spanish community sample. The sample consisted of 628 participants. The mean age was 27.5 (SD = 12.7) and 70.1% of them were women. The participants completed the PNEES, and measures of anxiety and depression (HADS), and eating disorder-related scales (TFEQ-R18, BULIT-R, and EAT-26) that were selected to examine convergent validity. A confirmatory factor analysis was conducted, replicating the original two-factor solution, consisting of Negative Emotional Eating (PNEES-N) and Positive Emotional Eating (PNEES-P). The results showed an acceptable fit of the model (CFI = .986; TLI = .984, RMSEA = .055). Internal consistency ranged from ω = .92 to ω = .96 for both subscales and the total score. PNEES-P correlations with other variables were lower with respect to the PNEES-N, showing that they are different constructs. A mediation analysis was conducted, in which PNEES-P significantly predicted binge eating and PNEES-N was a partially mediator variable. The results showed that the adaptation process was successful.